2007
DOI: 10.1007/s11249-007-9215-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lubricant Contamination on Gear Wear

Abstract: In this work the degradation of spur gears lubricated in a severe dusty environment studied. An experiment was carried out, which simulates the operation of gears in contaminated media such as the Sahara desert, quarries, or mines. The present study gives the effect of the presence of solid bodies in lubricants during surface contact. This paper shows that the use of a lubricant contaminated by very fine sand particles, leads to significant wear in the first few operating cycles, in zones with a high rate of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…5,6 The majority of studies are experimental. They cover the surface abrasion, indentation, erosion and scuffing by metallic particles of various sizes, hardness and toughness, mainly for sliding surfaces as in journal and sliding bearings in general, [7][8][9][10][11][12][13][14][15][16][17][18] spur gears, 19,20 engine cylinders and piston rings, [21][22][23][24][25][26][27][28] rails 29,30 and magnetic recording discs. 31 A large group of experimental and theoretical studies deals with the contact fatigue and life expectancy of debris-dented rolling contacts as in ball and roller bearings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The majority of studies are experimental. They cover the surface abrasion, indentation, erosion and scuffing by metallic particles of various sizes, hardness and toughness, mainly for sliding surfaces as in journal and sliding bearings in general, [7][8][9][10][11][12][13][14][15][16][17][18] spur gears, 19,20 engine cylinders and piston rings, [21][22][23][24][25][26][27][28] rails 29,30 and magnetic recording discs. 31 A large group of experimental and theoretical studies deals with the contact fatigue and life expectancy of debris-dented rolling contacts as in ball and roller bearings.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10]18,20,[64][65][66][67][68] They also govern the level of noise and vibration in the affected contacts. 19,[69][70][71] Obtaining this knowledge is achievable by parametrically analysing just a single particle. Results could then be extrapolated, at least for dilute suspensions, although such an extrapolation is not absolutely necessary because optimisation can be done based on the results by just one particle.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical thermal criteria are also presented for a particle size limit to avoid flash temperature scuffing failures from particles embedding in a bearing at a sliding surface contact. Sari et al presented an original experimental study, showing the effect of solid particles on gear wear. They demonstrated that the presence of sand particles in oil suspension leads to a significant wear of spur gear in the first few operating cycles in the zones with a high rate of sliding.…”
Section: Introductionmentioning
confidence: 99%
“…A temperature increase in SAE40 oil causes increase in both adhesive and corrosive wear [6]. Temperature also affects the concentration and distribution of oil contaminants, such as air, water, and particulates, which are usually unavoidable [7][8][9]. Three forms of water possibly exist in oil: dissolved water, emulsion, and free water.…”
Section: Introductionmentioning
confidence: 99%